Indexing and Querying Vague Spatial Data Warehouses - Siqueira, Thiago; Oliveira, João; Times, Valéria; Ciferri, Cristina; Ciferri, Ricardo (Journal of Information and Data Management, 2014)
A vague spatial data warehouse allows multidimensional queries with spatial predicates to support the analysis of business scores related to vague spatial data, crisp spatial data and conventional data. However, vague spatial data are often represented and stored as multiple geometries and impair the query processing performance. In this paper, we describe an index called VSB-index to improve the query processing performance in vague spatial data warehouses, focusing on range queries and vague regions. We also conduct an experimental evaluation using a real dataset, demonstrating that our VSB-index provided remarkable performance gains up to 94% over existing solutions.